PERBEDAAN PROFIL PROTEIN PADA TAHU SUTERA, TAHU KUNING DAN TAHU PONG METODE SDS-PAGE - Raden Bagus Muhamad Tsabitul Fikriyansyah; Meka Faizal Farabi; Dini Puspodewi (LPPM Universitas Abdurrab, 2025)
A food made from soybeans has a nutritional content in the form of protein, namely tofu. The principle of making tofu is made from white soybeans and the process is soaked in water, ground until smooth, boiled, filtered then separate the tofu dregs and filtrate (water) and added coagulants and food additives (BTP) then molded, but there are differences in the process of making tofu. Silken tofu has a soft texture and the process of making the curd is not pressed and not separated from the liquid so it resembles jelly. Yellow tofu has a yellow color from the addition of turmeric juice solution in the manufacturing process and its dense texture. Pong tofu has a distinctive feature after the manufacturing process is fried first before being packaged. To determine the differences in protein profiles, protein profile analysis was carried out using the SDS-PAGE method, for samples of silken tofu, yellow tofu and raw pong tofu. This type of research is descriptive analytical. The first analysis of total protein content with a standard curve and using a UV-Vis spectrophotometer, then continued with protein profile analysis using an SDS-PAGE electrophoresis tool. Results of total protein content and protein profile Silken tofu has a total protein content of 0.63 µg/µL and 1 protein band. Yellow tofu has a total protein content of 0.79 µg/µL and 2 protein bands. Pong tofu has a total protein content of 1.10 µg/µL and 4 protein bands. The difference in the process of the three tofus can affect the protein content of tofu, which can increase or decrease